Siah2 antagonism of Pard3/JamC modulates Ntn1-Dcc signaling to regulate cerebellar granule neuron germinal zone exit - Christophe Laumonnerie; Maleelo Shamambo; Daniel R. Stabley; Tommy L. Lewis; Niraj Trivedi; Danielle Howell; David J. Solecki (Nature Communications)
Abstract Exiting a germinal zone (GZ) initiates a cascade of events that promote neuronal maturation and circuit assembly. Developing neurons and their progenitors must interpret various niche signals—such as morphogens, guidance molecules, extracellular matrix components, and adhesive cues—to navigate this region. How differentiating neurons in mouse brains integrate and adapt to multiple cell-extrinsic niche cues with their cell-intrinsic machinery in exiting a GZ is unknown. We establish cooperation between cell polarity-regulated adhesion and Netrin-1 signaling comprises a coincidence detection circuit repelling maturing neurons from their GZ. In this circuit, the Partitioning defective 3 (Pard3) polarity protein and Junctional adhesion molecule-C (JamC) adhesion molecule promote, while the Seven in absentia 2 (Siah2) ubiquitin ligase inhibits, Deleted in colorectal cancer (Dcc) receptor surface recruitment to gate differentiation linked repulsion to GZ Netrin-1. These results demonstrate cell polarity as a central integrator of adhesive- and guidance cues cooperating to spur GZ exit.